Luminance and chromatic signals interact differently with melanopsin activation to control the pupil light response - Barrionuevo, Pablo Alejandro (2016)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) express the photopigment melanopsin. These cells receive afferent inputs from rods and cones, which provide inputs to the postreceptoral visual pathways. It is unknown, however, how melanopsin activation is integrated with postreceptoral signals to control the pupillary light reflex. This study reports human flicker pupillary responses measured using stimuli generated with a five-primary photostimulator that selectively modulated melanopsin, rod, S-, M-, and L-cone excitations in isolation, or in combination to produce postreceptoral signals. We first analyzed the light adaptation behavior of melanopsin activation and rod and cones signals. Second, we determined how melanopsin is integrated with postreceptoral signals by testing with cone luminance, chromatic blue-yellow, and chromatic red-green stimuli that were processed by magnocellular (MC), koniocellular (KC), and parvocellular (PC) pathways, respectively. A combined rod and melanopsin response was also measured. The relative phase of the postreceptoral signals was varied with respect to the melanopsin phase. The results showed that light adaptation behavior for all conditions was weaker than typical Weber adaptation. Melanopsin activation combined linearly with luminance, S-cone, and rod inputs, suggesting the locus of integration with MC and KC signals was retinal. The melanopsin contribution to phasic pupil responses was lower than luminance contributions, but much higher than S-cone contributions. Chromatic red-green modulation interacted with melanopsin activation nonlinearly as described by a ''winner-takes-all'' process, suggesting the integration with PC signals might be mediated by a postretinal site.